Enhancing salt stress tolerance in Carthamus tinctorius L. through selenium soil treatment: anatomical, biochemical, and physiological insights - Fatemeh Fatahiyan; Farzaneh Najafi; Zohreh Shirkhani (BMC Plant Biology)
Abstract Selenium (Se) plays a crucial role in ameliorating the negative impact of abiotic stress. The present study was performed to elucidate the efficacy of soil treatment of Se in reducing salt-induced stress in Carthamus tinctorius L. In this study, three different levels of Na2SeO4 (0, 0.01, and 0.02 g kg− 1) and four levels of NaCl (0, 0.5, 1.5, and 2.5 g kg− 1) were applied. The findings revealed that while NaCl decreased seed germination parameters, growth characteristics, K+ content, relative water content (RWC), and photosynthetic pigments, it increased Na+ content, soluble carbohydrates, H2O2 content, and malondialdehyde (MDA) level. The application of Se showed a positive effect on seed germination and growth characteristics under salinity conditions, which is linked to alterations in anatomical, biochemical, and physiological factors. Anatomical studies showed that treatment with Se led to increased stem diameter, cortical parenchyma thickness, and pith diameter under salinity stress. However, variations in the thickness of the xylem and phloem did not reach statistical significance. The application of Se (0.02 g kg− 1) raised Na+ content (7.65%), K+ content (29.24%), RWC (15%), Chl a (17%), Chl b (21.73%), Chl a + b (16.9%), Car (4.22%), and soluble carbohydrates (11%) in plants subjected to NaCl (2.5 g kg− 1) stress. Furthermore, it decreased H2O2 (25.65%) and MDA (11.9%) in the shoots. The findings of the current study advocate the application of the Se-soil treating technique as an approach for salt stress mitigation in crops grown in saline conditions.